(untitled) (Práxis Educativa, 2023)
This experimental study, with quantitative focus and longitudinal cutting, aimed to verify possible changes in the memory and attention of students aged 7 and 8 years with the practice of urban dances in school. The final sample consisted of 65 students divided into an intervention and control group, submitted to two cognitive tests. In the first test, the control group reached in the pre and post-test, respectively, an average of 19.9 (Standard Deviation – SD = 1.98) and 19.2 (SD = 2.33), while the intervention group reached, respectively, 19.4 (SD = 2.47) and 21.5 (SD = 2.50) (p<0.05). In the second test, the control group increased its response time while the intervention group decreased. Significant improvements in the memory and attention of the group that received the intervention were identified and, with this, it is expected to approximate the content of the teachers, as well as to promote possible scientific advances on the subject. Keywords: Urban dances. Attention. Memory.